(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate psychophysiological function in patients after total hysterectomy due to cancer at the Department of Gynecological Surgery, K Hospital in 2023. Subjects: Patients aged 18 to 55 years who have undergone a total hysterectomy. Method: Cross sectional study. Results: 106 patients after cervical cancer surgery were interviewed using a set of DASS 21 and FSFI questionnaires. The main age is from 30-55 years old (89.62%), having a high school degree or higher (87.73%), living with a husband (84.91%), most of whom have just had surgery once (93.4%). There were 12.26% of patients with varying degrees of depression; 30.19% of patients showed varying levels of anxiety; 26.42% of patients showed signs of stress at different levels. 100% of patients had sexual physiological disorders, the average of total scale was 14.76 ±2.72; The scores for each area were pain (1.87/6), satisfaction (2.12/6), arousal (2.5/6), orgasm (2.72/6), lubrication (3.04/6), and desire (3.18/6). Conclusion: The proportion of patients after total hysterectomy due to cancer has a high rate of psychological and physiological changes, and more counseling and guidance on remedial measures are needed to improve the quality of life.